Value proposition design : how to create products and services customers want - Osterwalder, Alexander, ....-; Bernarda, Gregory, ....-; Pigneur, Yves, 1954-; Smith, Alan, ....- (Hoboken, N.J. : John Wiley & Sons, 2014)
The book will help you understand the patterns of great value propositions, get closer to customers, and avoid wasting time with ideas that won't work. You'll learn the simple but comprehensive process of designing and testing value propositions, taking the guesswork out of creating products and services that perfectly match customers' needs and desires. Practical exercises, illustrations and tools help you immediately improve your product, service, or new business idea. In addition the book gives you exclusive access to an online companion on Strategyzer.com.
Canvas. Customer profile ; Value map ; Fit -- Design. Prototyping possibilities ; Starting points ; Understanding customers ; Making choices ; Finding the right business model ; Designing in established organizations -- Test. What to test ; Testing step-by-step ; Experiment library ; Bringing it all together -- Evolve. Create alignment ; measure & monitor ; Improve relentlessly ; Reinvent yourself constantly ; Taobao : reinventing (e)-commerce.
Includes index.
Keywords: Customer services -- Management; Quality control; Production management -- Quality control; Business planning; Strategic planning; Customer relations